Flight school eaudiobook - Judge, Lita (Recorded Books Inc., 2014)
A persevering penguin is determined to fly in this adorably inspiring picture book from the creator of "Red Hat "and "Red Sled." Although little Penguin has the soul of an eagle, his body wasn't built to soar. But Penguin has an irrepressible spirit, and he adamantly follows his dreams to flip, flap, fly! Even if he needs a little help with the technical parts, this penguin is ready to live on the wind